Estimating biomass, fishing mortality, and "total allowable discards" for surveyed non-target fish. (2nd July 2014) - Shephard, Samuel; Reid, David G.; Gerritsen, Hans D.; Farnsworth, Keith D.
Abstract: Demersal fisheries targeting a few high-value species often catch and discard other "non-target" species. It is difficult to quantify the impact of this incidental mortality when population biomass of a non-target species is unknown. We calculate biomass for 14 demersal fish species in ICES Area VIIg (Celtic Sea) by applying species- and length-based catchability corrections to catch records from the Irish Groundfish Survey (IGFS). We then combine these biomass estimates with records of commercial discards (and landings for marketable non-target species) to calculate annual harvesting rates ( HR ) for each study species. Uncertainty is incorporated into estimates of both biomass and HR . Our survey-based HR estimates for cod and whiting compared well with HR -converted fishing mortality ( F ) estimates from analytical assessments for these two stocks. Of the non-target species tested, red gurnard ( Chelidonichthys cuculus ) recorded some annual HR s greater than those for cod or whiting; challenging "Pope's postulate" that F on non-target stocks in an assemblage will not exceed that on target stocks. We relate HR for each species to two corresponding maximum sustainable yield (MSY) reference levels; six non-target species (including three ray species) show annual HR s ≥ HR MSY . This result suggests that it may not be possible to conserve vulnerable non-target species when F is coupled to that of target species. Based on biomass, HR, and HR MSY, we estimate "total allowable catch" for each non-target species.